The Effect of Non-Dental E-Glass Fiber Position on the Flexural Strength of Fiber Reinforced Composite - Aziza, Mia Nur; Sari, Widya Puspita; Anggraini, Netta (FKG Universitas Syiah Kuala, 2025)
Fixed denture is a treatment used to replace missing teeth. Fiber Reinforced Composite using dental E-glass fiber is an alternative material due to its biocompatibility, good aesthetics, and adaptability to the oral cavity.However in Indonesia, its availibility is limited and the cost is relatively high. Non-dental E-glass fiber, which has been widely used in engineering sectors, has a composition that is largely similar to dental E-glass fiber. This study aims to understand the effect of the position of non-dental E-glass fiber on the flexural strength of Fiber Reinforced Composite. This experimental study tested Fiber Reinforced Composite with non dental E-glass fiber placed in various positions using a Universal Testing Machine (UTM), and the results were analyzed with One-Way ANOVA. The test results showed that Fiber Reinforced Composite with fiber positioned on the tension side has the highest flexural strength, at 213.11 MPa, while placement on the compression side has the lowest value of 179.98 MPa. It was concluded that the position of non-dental E-glass fiber affects the flexural strength of Fiber Reinforced Composite.